f(3)=3(3)-1=8
g(0)=2(0)^2+1=1
so f(3)+g(0)=9
2006-12-29 11:36:54
·
answer #1
·
answered by raj 7
·
2⤊
0⤋
F(3)=3(3)-1+G(0)=2(0)^2+1
9-1+0+1=9
2006-12-29 11:51:45
·
answer #2
·
answered by Anonymous
·
1⤊
0⤋
F(3) + G(0) = 3*3 - 1 + 2*0*0 + 1 = 9 - 1 + 0 + 1 = 9
2006-12-29 11:37:29
·
answer #3
·
answered by Anonymous
·
2⤊
0⤋
3(3) - 1 + 2(0^2) + 1 = 9
2006-12-29 11:36:37
·
answer #4
·
answered by I know some math 4
·
2⤊
0⤋
F(3) means x=3 in the F(x) equation so F(3)= 3*3-1.
G(0) means put x=0 in the G(x) equation so G(0) = 2*0^2 +1.
add them together and you get 9.
2006-12-29 11:39:52
·
answer #5
·
answered by CAM1122 3
·
2⤊
0⤋
9
2007-01-02 10:22:20
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
9
2006-12-29 11:58:48
·
answer #7
·
answered by anonimous 6
·
1⤊
0⤋
9
2006-12-29 11:38:02
·
answer #8
·
answered by sexy prawn 3
·
1⤊
0⤋
*Take each number and replace it with "x" in the equation:
1. F(3) = 3(3) - 1
F(3) = 9 - 1
F(3) = 8
2. G(0) = 2(0)^2 + 1
G(0) = 0^2 + 1
G(0) = 0 + 1
G(0) = 1
Second: solve according to order of operations > F(3) + G(0)
8 + 1 = 9
2006-12-29 16:58:53
·
answer #9
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
f(3) = 3(3) - 1 = 9 - 1 = 8
g(0) = 2(0)^2 + 1 = 2(0) + 1 = 0 + 1 = 1
f(3) + g(0) = 8 + 1 = 9
f(3) + g(0) = 9
2006-12-29 12:47:51
·
answer #10
·
answered by Sherman81 6
·
2⤊
0⤋
f(3)= 3(3)-1
=9-1
=8
g(0)= 2(0)^2+1
=0+1
=1
8+1=9
9
2006-12-29 11:36:32
·
answer #11
·
answered by leksa27 2
·
2⤊
0⤋